A New Role for Estrogen Receptor α in Cell Proliferation and Cancer: Activating the Anticipatory Unfolded Protein Response - Livezey, Mara; Kim, Ji Eun; Shapiro, David J. (Frontiers in Endocrinology, 2018)
Cells react to a variety of stresses, including accumulation of unfolded or misfolded protein, by activating the endoplasmic reticulum (EnR) stress sensor, the unfolded protein response (UPR). The UPR is highly conserved and plays a key role in the maintenance of protein folding quality control and homeostasis. In contrast to the classical reactive mode of UPR activation, recent studies describe a hormone-activated anticipatory UPR. In this pathway, mitogenic hormones such as estrogen (E2), epidermal growth factor (EGF), and vascular endothelial growth factor (VEGF) rapidly activate the UPR in anticipation of a future need for increased protein folding capacity upon cell proliferation. Here, we focus on this recently unveiled pathway of E2-estrogen receptor alpha (ERalpha) action. Notably, rapid activation of the anticipatory UPR pathway is essential for subsequent activation of the E2-ERalpha regulated transcription program. Moreover, activation of the UPR at diagnosis is a powerful prognostic marker in ERalpha positive breast cancer. Furthermore, in cells containing ERalpha mutations that confer estrogen independence and are common in metastatic breast cancer, the UPR is constitutively activated and linked to antiestrogen resistance. Lethal ERalpha-dependent hyperactivation of the anticipatory UPR represents a promising therapeutic approach exploited by a new class of small molecule ERalpha biomodulator.